2020
DOI: 10.13106/jafeb.2020.vol7.no8.705
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Healthcare Expenditures in GCC Countries: A Panel Data Analysis

Abstract: This study aims to investigate the main factors that affected the government health expenditures in Gulf Cooperation Council (GCC) countries (Kingdom of Saudi Arabia (KSA), United Arab Emirates (UAE), Oman, Qatar, Bahrain and Kuwait), during the period from 2005 to 2019. The study employs a panel data technique in order to monitor the pooled determinant variables of healthcare expenditures in these countries. The study's results indicate, by using FMOLS approach for panel data, that the average healthcare expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Healthcare expenditures can be affected by industrialization, urban population, and economic growth [ 6 ]. A developed model investigated the factors determining government expenditure on healthcare and found that expenditures are significantly affected by variables related to government revenues, population, and government debt [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare expenditures can be affected by industrialization, urban population, and economic growth [ 6 ]. A developed model investigated the factors determining government expenditure on healthcare and found that expenditures are significantly affected by variables related to government revenues, population, and government debt [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor that Zhou et al [ 2 ] discovered was that there should be an effort on financial stability to ensure that there is universal access to healthcare at the same time activities as broadening of the revenue base through various means such as agriculture, industrialization is intensified. Ali & Sayed, [ 18 ] also investigated the factors that affect government healthcare spending in Gulf Council (GCC) nations. The study discovered that average healthcare spending per capita in GCC nations have a significant relationship with the revenue of the government, the population size, and the public debt of the nation.…”
Section: Introductionmentioning
confidence: 99%